The Implementation of Hypnoteaching Method in Increasing Motivation to Learn English for Senior High School in Pekanbaru - ardiya ardiya; Wandi Syahfutra (Universitas Lancang Kuning, 2021)
This study explores hypnoteaching method to increase students’ senior high school Pekanbaru motivation in learning English. Using a quantitative approach with a quasi-experimental design and provide pre-test and post-test to the both control class groups and experimental groups where SMA Handayani students and SMA PGRI students as research participants. The findings showed that 1) low student motivation is one of the causes of low student learning outcomes, 2) a classroom atmosphere to support the learning process is not built yet, 3) teachers do not found yet the right method to increase and keep students learning motivation. Based on the results of the research data processed using the paired-sample t test, there were found significant differences, namely before and after implementing the hypnoteaching method in learning English with alpha results less than 0.05. This study is beneficial in enriching literature in the scope of English education study programs, especially in Indonesia and others adopting English as a foreign language as a matter of applying appropriate and a more effective learning methods.